Effects of Prosopis africana (Guill. & Perr.) Taub. and Ficus mucoso Ficalho ethanolic leaves extract in the control of Callosobruchus maculatus (Fabricius, 1775) in stored cowpea - Tosin Damilola OJUYEMI (University of Ljubljana, Biotechnical Faculty, 2021)
The study investigated the effectiveness of Prosopis africana and Ficus mucoso ethanolic leave extract in the control of Callosobruchus maculatus infesting cowpea. Treatments were applied at different concentrations (10 %, 30 % , 50 %, and 0 %) on cowpea. Five pairs of newly emerged adult C. maculatus were introduced into each treatment. The two botanicals were evaluated on the insecticidal effects it has on the insect and data were recorded on adult mortality, oviposition rate, larvae, pupae, and adult emergence, seed viability, and phytochemicals present in both botanicals. Results revealed that both treatments had insecticidal potentials, adversely reducing the number of eggs, larvae, and pupae of C. maculatus with P. africana having the highest mean mortality rate at 50 % concentration. Observations further indicated that the botanicals had no negative effect on seed viability. The phytochemical analysis revealed the presence of some bioactive compounds such as terpenoids, flavonoids, alkaloids, saponin, steroids, and tannin, P. africana mostly rich in them than F. mucoso. Though both extracts were effective, P. africana performed better in the control of the bruchid beetle indicating plausible usefulness in sustainable pest management by smallholder farmers and consumers of cowpea in environments where the plants are in abundance.